Analyzing Thai Border School Policy Formation in the ASEAN Community Era - Ampa Kaewkumkong (Center for Southeast Asian Social Studies (CESASS), 2019)
During the 1990s, Thailand’s border areas became more open as a result of improved political relations in the region, especially in regards to the promotion of border trade and transnational trade among Indochinese countries under the“From a Battlefield to a Marketplace” policy. In terms of education development,the nature of border schools in general has been gradually evolving over the past 60 years, and Thai border schools have improved considerably over this period.The first initiative undertaken in regards to border schools in Thailand was the official establishment of the “Border Patrol Police (BPP) School” in 1956. Inmore recent years, education development policy in border areas has repeatedlybeen modified, particularly since Thailand’s agreement to further integrate withother Southeast Asian countries as a part of the ASEAN Community 2015. In 2010, Thailand’s commitment to developing its border schools increased whenit began development of the “Buffer School” program as part of a strategic plan to improve educational institutions under the ASEAN “Spirit of ASEAN” policy.This policy aimed to promote education development and cooperation within the ASEAN through a range of initiatives, including ones pertaining to border areas. This paper thus aims to 1) review the substance of the Buffer School program as it pertains to emerging Thai border school policy in the ASEAN Community era, as well as the structure of its enforcement, then, 2) analyze the background and rationale of policymaking that has occurred from agenda-setting and policy formulation up until policy enactment corresponding to ASEAN frameworks derived from the ASEAN charter and Work Plan on Education.